Molecular analysis of lipid uptake- and necroptosis-associated factor expression in vitrified-warmed mouse oocytes - Da-Eun Um; Hyejin Shin; Dayoung Park; Jeong Min Ahn; Jayeon Kim; Haengseok Song; Hyunjung Jade Lim (BMC, 2020)
Abstract Background We had previously demonstrated that vitrification reduces the levels of certain phospholipid classes, and that oocytes from aged mice show a similar lipidome alteration, even without vitrification. In the current investigation, we examined if vitrification-warming of mouse oocytes from young and aged mice causes any changes in molecular aspects of lipid-associated features. Methods Metaphase II (MII) stage oocytes were harvested from young (10-14-week-old) and aged (45-54-week-old) mice by a superovulation regime with PMSG followed by hCG. We examined the status of the intracellular lipid pool and the integrity of the plasma membrane by staining oocytes with BODIPY 500/510 and CellMask live dyes. Expression of lipid uptake- and necroptosis-associated genes was assessed by quantitative PCR analyses, in oocytes from young and old mice, before and after vitrification. Localization patterns of two crucial necroptosis proteins, phosphorylated MLKL (pMLKL) and phosphorylated RIPK1 (pRIPK1) were examined in mouse oocytes by immunofluorescence staining. Necrostain-1 (Nec1), an inhibitor of RIPK1, was used to examine if RIPK1 activity is required to maintain oocyte quality during vitrification. Results We confirmed that vitrified-warmed oocytes from aged mice showed noticeable decrease in both CellMask and BODIPY 500/510 dyes. Among the lipid uptake-associated genes, Cd36 expression was higher in oocytes from aged mice. Necroptosis is a type of programmed cell death that involves damage to the plasma membrane, eventually resulting in cell rupture. The expression of necroptosis-associated genes did not significantly differ among groups. We observed that localization patterns of pMLKL and pRIPK1 were unique in mouse oocytes, showing association with microtubule organizing centers (MTOCs) and spindle poles. pMLKL was also localized on kinetochores of MII chromosomes. Oocytes treated with Nec1 during vitrification showed a decreased survival rate, indicating the importance of RIPK1 activity in oocyte vitrification. Conclusions We report that oocytes from aged mice show differential expression of CD36, which suggests that CD36-mediated lipid uptake may be influenced by age. We also show for the first time that pMLKL and pRIPK1 exhibit unique localization pattern in mouse oocytes and this may suggest role(s) for these factors in non-necroptosis-associated cellular processes.